The delivery of palliative and end-of-life care to adolescents and young adults living with cancer: a scoping review protocol. Issue 12 (26th December 2021) - Drake, Emily K.; Weeks, Lori E.; van Manen, Michael; Curran, Janet; McKibbon, Shelley
ABSTRACT: Objective: This review will provide an overview of the evidence on the delivery of palliative and end-of-life care to adolescents and young adults living with cancer, by identifying knowledge gaps and discussing the key characteristics and types of evidence in this field. Introduction: Adolescents and young adults receive their diagnoses at an important stage of development, and often access health systems that are ill-equipped to deal with them, leading to many unmet needs. Some of these needs can be addressed by holistic palliative care services. A better understanding of the literature in this area is needed to identify what is known about the delivery of care to adolescents and young adults. Inclusion criteria: This review will consider studies that pertain to the delivery of palliative and end-of-life care for adolescents and young adults living with cancer. Relevant research may be in the context of ambulatory services, advance care planning, palliative care units, home care, hospices, and end-of-lifecare facilities. Studies that concern other oncology populations will be excluded. Methods: CINAHL (EBSCO), MEDLINE (Ovid), Embase (Elsevier), APA PsycINFO (EBSCO), and Web of Science (Science Citation Index Expanded and Social Sciences Citation Index; Clarivate Analytics) databases will be searched, along with other sources of gray literature. No date limit will be set. Two independent reviewers will screen titles and abstracts for studies that meet the review's inclusion criteria and the fulltext of eligible studies will be reviewed. Data from studies that are eligible for inclusion will be extracted using two independent reviewers and presented in a tabular form with an accompanying narrative summary.